(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: This study aimed to report the outcome of total hip arthroplasty (THA) with an extensive hydroxyapatite (HA) coating for the fixation of a tapered femoral stem (Corail) in patients younger than fifty years with osteonecrosis of the femoral head. Subject and method: Seventy-four osteonecrotic hips in fifty-eight patients were available for clinical and radiographic analyses at minimum follow-up of 10 years and at maximum follow-up 12 years. Results: The mean Harris hip score improved from 41.68 ± 21,78 points preoperatively to 98.82 ± 2.29 points at final follow-up. Seventy-four (100%) hips demonstrated stable bone ingrowth. No hips showed loosening or required revision for aseptic loosening. Conclusion: We believe that cementless THA with a Corail stem is a promising procedure for young patients with osteonecrosis of the femoral head.